@Stories.of the pandemic: educational media on the effects of social isolation during the COVID-19 pandemic (Research, Society and Development, 2021)
Objectives: to identify changes brought about by the COVID-19 pandemic, as well as develop educational media on the effects of social isolation imposed by the pandemic. Method: cross-sectional, exploratory, descriptive study, with a quali-quantitative approach, with a non-probabilistic sample and a convenience bias. A questionnaire was applied electronically and investigated sociodemographic data and psychological, work, social and family repercussions of social isolation, painful or adverse symptoms, and use of social media during the pandemic. Educational media were created, pointing out the main findings. Results: 140 people answered the questionnaire, 103 women (73.6%) and 37 men (26.4%). It was observed that 83.6% of the participants reported changes in the family relationship; 54.3% reported the presence of symptoms such as weight gain, pain, headache and decreased physical fitness. Among the 97 participants who perform work activities, 71.1% miss the work environment and 65.0% are working in a home office. Among the changes in behavior, irritability, anxiety or anguish were listed; sadness; weight gain or loss; energy loss or severe fatigue; insomnia; constant feeling of tiredness; excessive worries; muscle tension; oversleeping; change of appetite, among others. The educational media were broadcast and are available on the project's social network Instagram®, @historias.da_pandemia. Final Considerations: considering the current pandemic scenario, educational media will be able to contribute as instruments of active methodologies in the discussion and deepening of the theme, in basic, higher and informal education. They may also contribute to the development of new studies and adoption of intervention measures in the treatment of deleterious effects, mainly related to mental health.